Annual review of the sociology of religion - Berzano, Luigi.; Giordan, Giuseppe.; Pace, Enzo. (Annual Review of the Sociology of Religion, 2012)
This volume points to methodological innovations in social research and their potential for social scientific studies of religion. Computerization has opened for both quantitative and qualitative systematic analyses of complex materials, and the epistemological discourse after Positivism has opened for reconsidering the foundation of empirical social research. Furthermore religion is changing, and sociology of religion therefore widens its scope by including non-institutional forms of religion. This refocusing calls for new methodological considerations. As the range of available methods expands, it becomes more pressing to consider whether and how methods can be combined, such as quantitative and qualitative methods. Studying religion as a complex social phenomenon calls for a variety of methods, but an integration of the empirical findings points back to the epistemological issue.